ANALISIS PROPORSI BIAYA BENIH DAN PERBANDINGAN PRODUKTIVITAS USAHATANI PADI VARIETAS CIGEULIS DAN VARIETAS INFARI DI KAMPUNG JAMBUK MAKMUR - Mulyati Mulyati; Syarifah Aida; Mariyah Mariyah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2023)
Seed is one input in agricultural production for food availability. Farming in Jambuk Makmur cultivate paddy with two varieties: Cigeulis and Infari. This research aimed to determine the proportion of seed costs on cost production and to compare the productivity of paddy farming. The research was conducted in Jambuk Makmur Village Bongan District  Kutai Barat Regency from January to March 2022. Sampling used the Disproportionate Stratified Random Sampling method with a total sample of 20 rice farmers of the Cigeulis variety and 20 farmers of the Infari variety. Data analysis was done using farm costs analysis and an independent sample t-test. The results of this study showed that the average use of seeds of Cigeulis and Infari varieties per planting season was 35,54 Kg /ha and 39,54 Kg/ha. The average cost of seeds for the Cigeulis variety was IDR.841.875,00 per hectare, and the average cost of farming was IDR.16.665.361,57 per hectare. The percentage of seed costs to farming costs was 5,05%. The average cost of seeds for the Infari variety was IDR.484.750,00, the average cost of farming was IDR.17.466.305,95 mt-1 ha-1, and the percentage of seed costs to farming costs was 2,78%. Productivity of Cigeulis higher than Infari with productivity as 3.070,17 kg/ha  and 2.359,63 kg/ha.